Ecuador : Staff Report for the 2019 Article IV Consultation and Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Ecuador. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Ecuador's 2019 Article IV Consultation and Request for an Extended Arrangement under the Extended Fund Facility. The Article IV discussions focused on diagnosing the nature of the imbalances facing Ecuador and the policy changes that will be needed to address them. There was broad agreement that fundamental supply-side efforts will be needed to foster competitiveness, create jobs, rebuild institutions, and make Ecuador a more attractive destination for private investment. Consistent with the findings of the Article IV, the authorities' policy plan seeks to decisively address the systemic vulnerabilities facing Ecuador. The goals of these policies are to boost competitiveness and job creation, protect the poor and most vulnerable, fortify the institutional foundations for dollarization, and to improve transparency and good governance to public sector operations while strengthening the fight against corruption. The report suggests that improving the social safety net and increasing the effectiveness of public spending, particularly on health and education, will be essential to achieving strong, sustained, and socially equitable growth.